Mental Health Literacy Regarding Depression and Suicide - David Dias NETO; Pramod Lacmane MAUGI (European Journal of Mental Health, 2022)
Introduction: Mental health literacy enables individuals to recognize the symptoms associated with mental illness, and thus adjust their behavior to manage and seek help and treatment for mental illness. Aims: The present research aims to study determinants of mental health literacy and whether an association exists between mental health literacy and the understanding of content related to depression and suicide. Methods: In each group, the participants read one leaflet about depression or suicide and answered a questionnaire to assess their understanding. All the participants also filled out a mental health literacy self-report. Results: The results showed higher mental health literacy for women and individuals with a higher education. Mental health literacy predicted the understanding of suicide content, but the same did not apply for depression. Conclusions: Mental health literacy stands as an important factor to be considered in developing campaigns and promotional actions. However, its effect remains contingent on the contents and context. It is crucial to consider this interaction in maximizing the campaigns’ impact on the population.